The Impact Of Peer Review On Writing Instruction: Exploring Students' Learning Motivation At SD Marsudirini Semarang - Syarifa Manullang; Puji Astuti; Rudi Hartono (English Education Journal, 2025)
This study aims to investigate the impact of peer review on writing instruction and students' learning motivation. Conventional teaching methods were found to be ineffective, leading to low student engagement and poor writing scores. By incorporating the peer review technique, the experimental group demonstrated significantly higher levels of participation and improved writing performance than the control group. These findings highlight the potential of Peer review by applying a mixed-method type, quasi-experiment research design (quantitative research – test) and (qualitative research – observation and questionnaire). The results of the student's participation in the control class were 2.95, with a moderate degree level. Meanwhile, the results of the peer review questionnaire in increasing the motivation of experimental class students were 3,76 with a high degree level. A statistical test will determine whether peer review has impaction and writing ability through an independent sample t-test using SPSS 29. As a result, Peer review effectively enhances students' writing ability with a mean of 76. It means that the experimental class students' writing ability scores are in a suitable category.